Factors that limit customer value in touristic facilities, as perceived by managers and specialists - Zambrano Cancañón, Carlos Ernesto (2020)
Fil: Zambrano Cancañón, Carlos Ernesto. Holguín University. Faculty of Economics and Business Administration; Cuba.